AN OVERVIEW OF THE PROMISING APPROACH TO ENHANCE THE PHYSICAL PROPERTY OF API BY PHARMACEUTICAL CO-CRYSTALLISATION TECHNIQUE - Shiwangi Jain; Mayank Bansal (Journal of Biomedical and Pharmaceutical Research, 2020)
Co-crystals are defined as crystalline complexes of two or more neutral molecular constituents bound together in the crystal lattice through non covalent interactions. This article summarized about the co-crystal definition, its importance along with characterizations and screening and production methods. From the literature survey, it can be concluded that improvement of performance characteristics of APIs using co-crystallization is a shows potential approach. One of the key aspects of this technique is that it can be useful to all APIs affliction from poor aqueous solubility.  Co-crystallization moves toward is flourishing now adays due to its immaculate effect of solubility on poorly dissolvable drugs, especially those having weakly ionisable group and neutral compounds. Meanwhile co-crystallization will also put an effort into upgrading of other physicochemical properties of drugs such as chemical stability, flowability etc.Keywords: Co-crystals, characteristics, screening, productions, solubility